A fungus-eat-fungus world: Digitopodium, with particular reference to mycoparasites of the coffee leaf rust, Hemileia vastatrix - Adans A. Colmán; Harry C. Evans; Sara S. Salcedo-Sarmiento; Uwe Braun; Kifle Belachew-Bekele; Robert W. Barreto (IMA Fungus)
Abstract Digitopodium hemileiae was described originally in 1930 as Cladosporium hemileiae; growing as a mycoparasite of the coffee leaf rust (CLR), Hemileia vastatrix, in a sample of diseased leaves of Coffea canephora collected in the Democratic Republic of Congo. No cultures from this material exist. More recently, the type material was re-examined and, based on morphological features, considered to be incorrectly placed in Cladosporium. The new genus Digitopodium was erected to accommodate this species. Interest in fungal antagonists of H. vastarix, as potential biocontrol agents of CLR, led to comprehensive surveys for mycoparasites, both in the African centre of origin of the rust, as well as in its South American exotic range. Among the rust specimens from Ethiopia, one was found to be colonized by a fungus congeneric with, and similar to, D. hemileiae. Pure cultures obtained from the Ethiopian material enabled a molecular study and for its phylogenetic position to be elucidated, based on DNA sequence data from the ITS and LSU regions. Molecular data showed that two members of the recently erected genus Hyalocladosporiella (Herpotrichiellaceae: Chaetothyriales) are congeneric with Digitopodium from Ethiopia and morphologically similar to both D. hemileiae and the two Ethiopian isolates. These isolates were found to be morphologically and genetically identical to H. tectonae, described previously from Brazil. Thus, species of Hyalocladosporiella are re-allocated to Digitopodium here; including D. tectonae, and a novel species, D. canescens, recently found in Brazil growing as a mycoparasite of Puccinia thaliae. The potential use of D. hemileiae and D. tectonae for classical biological control of CLR is discussed.